İdentification of genetic polymorphism and dna methylation pattern in wheat (triticum aestivum l.) - (:unkn) unknown (My University, 2011)
0

SSR, RAPD, ISSR and SRAP markers have been used to examine the genetic and epigenetic diversity of wheat (Triticum aestivum L.) germplasm. PCR amplification of the DNA isolated from six wheat genotypes yielded a total of 2118 amplified products, of which 1105 were polymorphic and 1013 were monomorphic. The average PIC value for all molecular marker data was 0.8704 and average percentage of polymorphism was 40.86%. All primers used for RAPD analysis, were also tested by CRED-RA analysis, a method to detect DNA methylation. There were differences between genetic and methylation polymorphism in the studied cultivars. Dendrogram created based on genetic polymorphism showed that PI178383 and Sonmez2001 (0.30) were genetically very different from each other, but in the dendrogram constructed by methylation polymorphism Sonmez2001 and ES14 (0.44) were grouped in one subcluster. Similar to this, in the dendrogram created based on epimarker data Izgi2001 and Harmankaya99 (0.59) were grouped in one subcluster as well as Sonmez2001 and ES14 (0.57) as in the second sub-cluster. The present study has provided the genetic data that diagnose the level of polymorphisms and epigenetic data which present natural variations of DNA methylation.
Keywords: Ziraat Mühendisliği